DECENTRALIZATION OF POWER IN UKRAINE AND EUROPE: SECURITY AND FINANCE ISSUES - O. A. Muzyka-Stefanchuk; O. O. Otradnova; N. L. Huberska; N. Ya. Borsuk; V. G. Savenkova (Фінансово-кредитна діяльність: проблеми теорії та практики)
The decentralization is not a new phenomenon for Ukraine. The processes, directed to establish and to develop the local self-government according to European model, going away from complete subordination of local power to the state power during Soviet times, were activated since the state acquired the independence.